UV-protective compound-containing smart textiles: A brief overview - Lupino, João Henrique Barcha; Saito, Gustavo Pereira; Cebim, Marco Aurélio; Davolos, Marian Rosaly (Eclética Química, 2023)
Excessive exposure to solar ultraviolet (UV) radiation causes human health damages, such as sunburns and skin cancer. Thus, the use of sun-protective clothing is a simple, easy, and practical method for UV protection of the human organism. In this perspective, incorporation, coating, and anchorage of UV-protective compounds in textile fibers have been employed to enhance the UV-blocking ability and/or promote functional finishings to smart fabrics. This review describes recent research efforts on the development of UV-protective compound-containing smart fabrics highlighting the UV-blocking properties and multifunctional activities. Different compound class examples and discussions are presented in order to contribute to new insights into sun-protective clothing and future applications of multifunctional textiles.